Statistics of education in Nigeria. (Lagos: Federal Ministry of Information, Print. Division, 1963)
This volume includes statistics related to education like number of schools, teachers, types of educational institutions (Technical, educational, vocational) levels (primary, secondary, tertiary).
lje 23/11/19
Ref
Keywords: Education; Nigeria